In silico пошук gvp-кластерів Streptomyces globisporus 1912-2 - Поліщук, Л.В. (Фактори експериментальної еволюції організмів, 2015)
The aims – to find of gvp-clasters in the genome of S. globisporus 1912-2. Methods. The programs BLASTN were used for in silico analysis of the S. globisporus 1912-2 contigs library. Results. Two gvp-clusters in the library of S. globisporus 1912-2 chromosome fragments were found. One gvp-cluster was localized on Contig 264, the second cluster – on Contig 756 and Contig 781. Both gvp-clusters contain 10 genes in traditional order for streptomycetes cluster: gvpO - A - F - G - Y - Z - J - L - S - K. Conclusions. In silico analysis of the primary structures of two S. globisporus 1912-2 gvp-clusters did not find significant homology in their nucleotide sequences, therefore we could suggest that they were orthologous or significant changes in their primary structures occurred as a results of mutations after duplication. Keywords: Streptomyces globisporus 1912-2, gvp-claster, homology, chromosomal DNA.